Pengelolaan Sampah Berbasis 3R melalui Edukasi Digital dalam Meningkatkan Kepedulian Lingkungan Siswa SMP - Andi Zulitsnayarti Mardhani Syam; Thamrin Tahir; Alfiana Damasinta; Muhammad Ilyas Thamrin Tahir; Nurwahida Nurwahida (STMIK Pesat Nabire, 2026)
Waste management problems in schools remain a significant challenge that requires educational and participatory approaches. Students’ low awareness of 3R-based waste management (Reduce, Reuse, Recycle) can negatively affect the cleanliness and environmental quality of the school environment. This community service program aimed to improve students’ environmental awareness through the implementation of a 3R-based waste management program integrated with digital education at SMP Integral Luqman Al-Hakim. The implementation method employed educational and participatory approaches through several stages, including preliminary observation, development of digital educational media, material presentation, practical activities on 3R-based waste management, and program evaluation. The digital media utilized included interactive presentations, educational videos, and digital posters to enhance students’ interest and participation. The results showed an improvement in students’ understanding and environmental awareness, as reflected in their habits of disposing of waste properly, sorting organic and inorganic waste, and actively participating in simple recycling activities. Furthermore, the implementation of the 3R-based waste management program through digital education successfully fostered a culture of environmental awareness within the school and dormitory environment. Therefore, this program can serve as an educational effort to sustainably enhance students’ environmental awareness.